RETRACTED: Sustainable financial dimensions of managing poverty in the era of the COVID-19 pandemic: A developing country perspective - Lu, Shaohua; Dai, Junmin; Ali, Anis; Al-Faryan, Mamdouh Abdulaziz Saleh; Iqbal, Nadeem (Frontiers in Environmental Science, 2022)
The COVID-19 pandemic is dangerous to people's lives and livelihoods, creating immediate obstacles for organizations that support impacted populations. This research concentrates on the consequences for local microfinance institutions in Pakistan, a well-developed sector that serves many households to pull out of the poverty trap. Microfinance programs in Pakistan provide financial resources to vulnerable and deprived people to engage in income-generating practices on more favorable terms. As a result, this study addressed and assessed the financial dimensions of managing poverty reduction in rural Pakistan through the microfinance segment and its effectiveness on poverty reduction programs in Pakistan during the COVID-19 pandemic. The primary data was collected through a questionnaire survey to determine the views of households, beneficiaries, and non-beneficiaries on the outcome and efficacy of poverty reduction programs during the pandemic to meet the study objectives. The Mann-Whitney U-Test of the non-parametric method and Cronbach's alpha of data reliability test have been applied for the empirical analysis. According to the non-parametric findings, programs, marital status, working women members, and resources such as land, livestock, business assets, shares, and loans are all affected during COVID 19. Education, wages, gender, size, child dependency, and district variables are significant factors related to poverty, but they fall in the second position during COVID-19. The finding suggests that a small loan system must be improved and efficient during the pandemic. It could be one of the practical tools to maintain poor people's current economic and poverty position.